Synthesis of poly(styrene-co-methyl methacrylate)-based ionomers and their Langmuir and Langmuir-Blodgett (LB) film formation - Carvalho, AJF; Ferreira, M.; Balogh, D. T.; Oliveira, O. N.; Faria, R. M. (Amer Chemical Soc, 2004)
Poly(styrene-co-methyl methacrylate) (PS-PMMA) ionomers with several degrees of sulfonation were synthesized and characterized by infrared, UV-vis, and NMR spectroscopies, elemental analysis, and differential scanning calorimetry (DSC). Stable Langmuir films could be produced with PS-PMMA with 3 and 6 mol % of sulfonation, while PS-PMMA 8% exhibited material loss to the water subphase, probably due to its higher solubility. Surface pressure and surface potential isotherms with PS-PMMA 3% spread onto salt-containing subphases pointed to a film behavior characteristic of the polyelectrolyte effect, where charge repulsion governs the film properties. The Langmuir-Blodgett films of this ionomer were successfully transferred onto various substrates, as confirmed by UV-vis and FTIR spectroscopies. Using cycling voltammetry, we show that LB films from PS-PMMA 3% can be applied in selective sensing of dopamine, even in the presence of interferents such as ascorbic acid.